Free allocation rules in the EU emissions trading system: what does the empirical literature show?. (21st April 2019) - Verde, Stefano F.; Teixidó, Jordi; Marcantonini, Claudio; Labandeira, Xavier
ABSTRACT: This paper analyses the rules for free allocation in the EU Emissions Trading System (EU ETS). The analysis draws on the empirical evidence emerging from two literature strands. One group of studies sheds light on the following questions: how efficient are free allocation rules in minimizing the risk of carbon leakage? Have they become more efficient over the trading periods? What are the technical limits to making them more efficient? Further: is firm behaviour affected by allowance allocation? Did specific provisions induce strategic behaviour with unintended effects? Studies from the second group estimate sectoral pass-through rates for the costs imposed by the EU ETS. Taking cost pass-through into account is necessary for properly targeting free allocation. The difficulty of accurately quantifying sectoral differences in cost pass-through ability, especially in manufacturing sectors (due to limited data availability and market heterogeneity), is the main hindrance to achieving further efficiency in allowance allocation. The new rules defined in the reform for Phase IV (2021–2030) nevertheless make some progress in this direction. Key policy insights The difficulty of accurately quantifying sectoral differences in cost pass-through ability is the main hindrance to efficient free allocation in minimizing carbon leakage risk. In Phase IV (2021–2030), carbon leakage risk will be assessed more accurately thanks to: a) carbon intensity and trade intensity considered together through a combined indicator; b) possible use of more disaggregated data, and c) possible consideration of complementary qualitative assessments of abatement potential, market characteristics and profit margins. It is expected that benchmarked allocation introduced in Phase III (2013–2020) has induced additional emission abatement, but there is still a lack of empirical evidence.